The fatigue behavior and mechanism of FV520B-I with large surface roughness in a very high cycle regime. (August 2016) - Zhang, Ming; Wang, Weiqiang; Wang, Pengfei; Liu, Yan; Li, Jianfeng
Abstract: The fatigue properties of FV520B-I up to 10 9  cycles when the surface roughness R a  ≈ 0.6 were tested and compared with two groups of previously obtained test results. The test results showed that the S - N curve continuously moved downward and the transition stress at which the crack origin changed from the surface to the subsurface decreased with an increase of surface roughness, and the conventional fatigue limit finally appeared. The initiation mechanism of subsurface cracks in a very high cycle fatigue regime was independent of surface roughness. The surface fatigue limit and the high cycle fatigue life were predicted by relevant models. The competition mechanism between surface cracking and subsurface cracking was further discussed. Highlights: The fatigue properties of FV520B-I with large surface roughness in a very high cycle regime were tested. The effects of surface roughness on the VHCF behaviors and mechanisms of FV520B-I were analyzed. The surface fatigue limit and the high cycle fatigue life were predicted by relevant models. The competition mechanism between surface cracking and subsurface cracking was discussed.